Kojic acid in fourteen mono-solvents: Solubility data, Hansen solubility parameter and thermodynamic properties. (January 2021) - Sun, Renren; He, Haixia; Wan, Yameng; Li, Liyuan; Sha, Jiao; Jiang, Gaoliang; Li, Yu; Li, Tao; Ren, Baozeng
Highlights: Solubility of kojic acid in fourteen pure solvents was measured. The miscibility of kojic acid in solvents was revealed by Hansen solubility parameter. Experimental solubility was discussed and correlated by five thermodynamic models. The thermodynamic properties were evaluated by van't Hoff equation. Abstract: In this research, solubility of kojic acid in fourteen mono-solvents was obtained by laser monitoring approach at various temperatures under 0.1 MPa. The mole solubility of kojic acid exhibited a positive relation with temperature. Moreover, the solubility sequence of kojic acid at 298.15 K is: dimethyl sulfoxide (DMSO) > N-methylpyrrolidone (NMP) > N, N-dimethylacetamide (DMAC) > N, N-dimethylformamide (DMF) > 2-methoxyethanol > 2-ethoxyethanol > acetic acid > methanol > 1, 4-dioxane > ethanol > water > n-propanol > acetone > ethyl acetate. The Hansen solubility parameter (HSP) and solvents polarity were applied to explore this solubility behaviour. The experimental solubility data was correlated with five thermodynamic models including two-Suffix Margules, NRTL-SAC, NRTL, modified Apelblat equation and UNIQUAC model, and the calculated results indicated that all of models had great fitting effects with the measured solubility data. Furthermore, the solution thermodynamic properties (Δdis G o, Δdis H o, Δdis S o ) of kojic acid in investigated solvents were calculated by van't Hoff equation. The positive values of Δdis H o and Δdis S o indicated that the dissolution process of kojic acid in all the measured solvents was endothermic and entropy-driven.